2020
DOI: 10.5194/cp-2020-114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deoxygenation dynamics above the western Nile deep-sea fan during sapropel S1 at seasonal to millennial time-scales

Abstract: Abstract. Ocean deoxygenation is a rising threat to marine ecosystems and food resources under present climate warming conditions. Organic-rich sapropel layers deposited in the Mediterranean Sea provide a natural laboratory to study the processes that have controlled the changes in seawater oxygen levels in the recent geological past. Our study is based on three sediment cores spanning the last 10 thousand years (10 kyr BP) and located on a bathymetric transect offshore the western distributaries of the Nile d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(182 reference statements)
0
3
0
Order By: Relevance
“…Lines 473-475. The authors may cite a recent regional modelling study that simulated surface salinity anomaly distribution in the Mediterranean Sea by increasing Nile river discharge (Vadsaria et al, 2019).…”
Section: Discussion Papermentioning
confidence: 99%
“…Lines 473-475. The authors may cite a recent regional modelling study that simulated surface salinity anomaly distribution in the Mediterranean Sea by increasing Nile river discharge (Vadsaria et al, 2019).…”
Section: Discussion Papermentioning
confidence: 99%
“…3), with the criterion that the manuscript should be a research article. The manuscripts and articles, published with the Creative Commons Attribution 4.0 License, that the analysed text histories relate to are Blanchet et al (2021;acronym used in the examples TH1), Pawlak (2021; TH2) and Velasquez et al (2021;TH3). Analysing three manuscripts' text histories allows for comparison and contrast between the different manuscripts while still being a manageable amount of data to analyse.…”
Section: • Final Ed Lettermentioning
confidence: 99%
“…These past humid periods were characterized by enhanced freshwater discharge and sediment export from the large African river systems to surrounding ocean margins (Blanchet et al, 2021;Mologni et al, 2020;Skonieczny et al, 2015). A number of recent studies conducted at a high temporal resolution (10-1000 years) in lake and deltaic sedimentary records across northern Africa suggested that gradual long-term monsoon oscillations had been often punctuated by millennial-scale episodes of hyperaridity (Bastian et al, 2017;Berke et al, 2012;Blanchet et al, 2020;Castañeda et al, 2016;Collins et al, 2013;Costa et al, 2014;Foerster et al, 2012;Liu et al, 2017;Tierney et al, , 2011bTierney et al, , 2011aTierney et al, , 2008Verschuren and Russell, 2009), as exemplified by significant increase in aeolian dust deposition in sediment records from African margins (Bouimetarhan et al, 2012;Collins et al, 2017Collins et al, , 2013Heinrich et al, 2021;McGee et al, 2013;Tierney et al, 2017). These hyperarid episodes occurred contemporaneously with North Hemisphere cooling events recorded in Greenland ice cores (i.e.…”
Section: Introductionmentioning
confidence: 99%